2011
DOI: 10.1111/j.1365-4632.2010.04822.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib‐induced premalignant and malignant skin lesions

Abstract: The possibility of rapidly developing actinic keratoses, keratocanthomas, verrucas, and SCC during treatment with sorafenib, warrants close dermatologic follow-up and a lower threshold for biopsy and treatment of suspicious cutaneous lesions. Development of a sorafenib-induced SCC is not an absolute contraindication for continued use of sorafenib therapy; however, the drug should be briefly discontinued until lesions are treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
(140 reference statements)
0
31
0
Order By: Relevance
“…In the subgroup of patients with BRAF -mutant tumors, the PFS duration of those who received sorafenib was substantial (20.8 months) but not significantly different from that of those who received placebo (9.4 months), however, this could be explained by the different prognoses of the differing subtypes of DTC. 26 …”
Section: Advanced Thyroid Cancer Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subgroup of patients with BRAF -mutant tumors, the PFS duration of those who received sorafenib was substantial (20.8 months) but not significantly different from that of those who received placebo (9.4 months), however, this could be explained by the different prognoses of the differing subtypes of DTC. 26 …”
Section: Advanced Thyroid Cancer Managementmentioning
confidence: 99%
“…SCC and keratoacanthomas have also been seen in patients treated with sorafenib, another compound with inhibitory activity against RAF kinases 26,96,97 . Squamous cell tumors in patients treated with the BRAF inhibitors vemurafenib and sorafenib have a distinct mutational profile that indicates a mechanism of therapy-induced tumorigenesis in RAS-primed cells 98,99 .…”
Section: Adverse Effects Of Braf Inhibitors and Suggested Managementmentioning
confidence: 99%
“…Interestingly, many of these lesions are also encountered with the use of the multikinase inhibitor sorafenib, which also inhibits RAF [66,67]. Up to 11% of patients receiving sorafenib develop keratoacanthoma/cuSCC and actinic keratoses, with a median onset of 9 months [68].…”
Section: Cutaneous Toxicitymentioning
confidence: 98%
“…Furthermore, RAS protooncogen mutation was identified in about 40% of lesions (23). Other drugs that lead to the inhibition of RAF signaling pathway, such as sorafenib or dabrafenib, can also cause squamous cell skin carcinoma in up to 10% of all treated patients (24,25). Therefore it has been suggested that RAF inhibition has a direct role in secondary malignancy development in these patients.…”
Section: Kerathoacantoma and Squamous Cell Skin Carcinomamentioning
confidence: 99%